Zagotavljanje kakovosti v zdravstveni negi v Bolnišnici Golnik, Klinični oddelek za pljučne bolezni in alergijo Golnik - Kadivec, Saša (Obzornik zdravstvene nege, 2000)
The article presents quality assurance process in the Hospital for lung and allergic diseases Golnik, presenting the case of quality assurance of personalhygiene of a patient. The results of initial measurement were not satisfying but have, through planned activities, become better during the pasttwo years.
Keywords: bolnišnice; kvaliteta; pljučne bolezni; zdravstvena nega